Performance comparison between differential frequency hopping and fast frequency hopping - Guan, Jiajia. (2013)
Differential frequency hopping (DFH) is a frequency-hopping communication system with memory. The minimum sequence error method is proposed as the frequency sequence estimation algorithm. This algorithm can effectively reduce the illegal frequency transfer states through a searching method called the maximum-likelihood detection. The algorithm can improve the performance of DFH as well. In a fast frequency-hopping (FFH) system, the frequency-hopping rate is higher than the symbol rate, say 3 hops per bit, 5 hops per bit or 7 hops per bit.